The Impact of Interior and Exterior Design of Shopping Mall on Consumer Purchasing Intention- A Case Study of ODEL, Srilanka - Madhushani, B.R.P.T.; Selvarajan, P. (National Centre for Advanced Studies, Sri Lanka., 2019)
This research paper aims to identify the interior and exterior design of shopping mall and consumer purchasing intention. In today’s competitive retail industry, it is harder than ever to reach a target segment and sell a particular brand or a particular product to that segment. Therefore, retailers need to pay special attention to all elements of their retail mix which includes store design and atmosphere. Literature found that the interior and exterior design factors play a significant role in consumer purchase intention. The retail industry has grown in leaps and bounds, over the past decade. Researchers were interested in investigating the factors influencing the purchasing intention of consumers in one of the leading retailing outlet- ODEL in Sri Lanka. The main objective of this study is to identify the interior and exterior design of shopping mall and the consumer purchasing intention. Although the role of retail environment affects the consumer purchasing intention, it is to be proved with adequate evidences. Therefore, researchers used the qualitative case study method with interpretive analysis to find the richness of information. The data were collected through a semi-structured questionnaire, participant’s observation and interview from 50 regular customers of ODEL outlets in Colombo city. The findings show that there are several interior and exterior design factors play major role in the purchasing intention of consumers at ODEL shopping mall. Temperature in mall is considered as the most influential factor among the other factors of flooring, colours, lighting, scents, sounds, fixtures, merchandise, and cleanliness. Subsequently, the entrance of the mall plays a major role among the other exterior design factors such as display windows, physical characteristics of the building, surrounding area and parking. It was also found that compared with the exterior designs, the interior design was considered the most powerful and determining factor to the purchasing intention of buyers. It is recommended that the ODEL should adopt the modern interior and exterior designs with the help of modern technology and based on the luxury concept they must focus on outdoor windows, outdoor display and outside landscaping for attracting more consumers and practice a successful marketing.
Keywords: Exterior design; Interior design; Interpretive case study method; Purchasing intention